2021
DOI: 10.1038/s41467-021-23478-1
|View full text |Cite
|
Sign up to set email alerts
|

An antibody against L1 cell adhesion molecule inhibits cardiotoxicity by regulating persistent DNA damage

Abstract: Targeting the molecular pathways underlying the cardiotoxicity associated with thoracic irradiation and doxorubicin (Dox) could reduce the morbidity and mortality associated with these anticancer treatments. Here, we find that vascular endothelial cells (ECs) with persistent DNA damage induced by irradiation and Dox treatment exhibit a fibrotic phenotype (endothelial–mesenchymal transition, EndMT) correlating with the colocalization of L1CAM and persistent DNA damage foci. We demonstrate that treatment with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Numerous studies have discovered that different localized L1CAMs exerted different functions by mediating different mechanisms, and participated in various disease processes. Nam JK et al showed that fibrotic phenotype (endothelial–mesenchymal transition, EndMT) may be seen in vascular endothelial cells when persistent DNA damage has been caused by irradiation and subsequent treatment with Dox correlating with the colocalization of L1CAM and persistent DNA damage foci [ 18 ]. Moreover, the use of the anti-L1CAM antibody in therapy has the potential to attenuate L1CAM overexpression as well as nuclear translocation and persistent DNA damage foci [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have discovered that different localized L1CAMs exerted different functions by mediating different mechanisms, and participated in various disease processes. Nam JK et al showed that fibrotic phenotype (endothelial–mesenchymal transition, EndMT) may be seen in vascular endothelial cells when persistent DNA damage has been caused by irradiation and subsequent treatment with Dox correlating with the colocalization of L1CAM and persistent DNA damage foci [ 18 ]. Moreover, the use of the anti-L1CAM antibody in therapy has the potential to attenuate L1CAM overexpression as well as nuclear translocation and persistent DNA damage foci [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the investigation of the function of L1CAM in AF, as well as other cardiac disease, was extremely rare. By modulating the extent of persistent DNA damage, an antibody that targets the L1 cell adhesion molecule may suppress cardiotoxicity [ 18 ]. L1CAM was an essential component in the cell adhesion process, working in conjunction with neural cell adhesion molecule (NCAM).…”
Section: Introductionmentioning
confidence: 99%
“…DOX is the most widely used anthracycline in numerous neoplastic diseases, despite the fact that its cardiotoxicity is an important side effect [ 5 , 6 ]. In fact, in addition to causing acute toxicity that is reversible, DOX, over the years, can generate a progressive injury process, causing a dose-dependent risk of heart failure [ 5 , 6 , 7 ]. At the level of tumor cells, DOX inhibits proliferation and leads to cell death as it intercalates with DNA in the nucleus and inhibits topoisomerase IIα (Top IIα) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Among them, doxorubicin hydrochloride (DOX) is the most common anti-cancer drug that has frequently been reported to have been detected in sewage systems. 2,3 With the widespread use of DOX in tumor treatment, DOX enters groundwater and penetrates into the soil, causing DOX to accumulate easily in plants and eventually to enter the human body through the food chain. 4 Unfortunately, when DOX is accumulated to a certain extent, it will cause the body's immune system to decline and cause pollution to the natural environment.…”
Section: Introductionmentioning
confidence: 99%